(untitled) (Journal of Asian Development Studies, 2024)
The current study examined Social media addiction, body satisfaction, and subjective well-being among adolescents. For this purpose, the sample for the current study was calculated by the G power formula (F, t, χ2, Z, and exact tests) 300 participants were selected through the convenient sampling technique (139 Boys and 161 Girls), adolescents with the age range of 10-19 from different colleges and universities of Faisalabad. The Co-relational research design was used in the current study. The variables under research were measured using the following scales: The Bergen Social Media Addiction Scale (Andreassen et al., 2016), the Body Shape Questionnaire (Cooper et al., 1987), the Rosenberg Self-Esteem Scale (Rosenberg,1965), the Work & Social Adjustment Scale (Marks et al., 2002), ICP Subjective Well-Being Scale (Diener’s, 1984). Using SPSS version 26, descriptive statistics, correlation, and t-tests were used to evaluate the current research hypothesis. Results of the correlation analysis revealed that there is a significant negative relationship between social media addiction and body satisfaction. In contrast, body satisfaction and subjective well-being were significantly positively related, and subjective well-being with body satisfaction showed no ties. The findings will benefit adolescents and management in schools and universities by providing a healthy environment and social skills to reduce social media addiction. Excessive social media use negatively impacts adolescents’ body satisfaction and overall well-being. For adolescents, there is a need for educational programs and open communication to promote healthy online habits and to reduce social media’s negative effects, with parental support playing a crucial role.